J.B. Waid autograph note - Waid, J. B., 1804-
Photocopy of an autograph note by Waid.
Negative photocopy.
Canadian author and poet. Also known as the Bard of Niagara.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Authors, Canadian; Poets, Canadian; Authors; Poets